IDENTIFIKASI DAN ANALISIS FAKTOR RISIKO KEGAGALAN PENYEDIAAN PSU PERUMAHAN SUBSIDI DI INDONESIA - Meiky Susanto (Jurnal Infrastruktur, 2020)
In 2017, 36.42% of subsidized housing was not yet occupied by debtors. For this amount 45.02% was caused by poor public infrastructure and facilities (PIF) conditions. This study is dedicated to analyzing the root of the problem and how much its influence of the failure factors in PIF provision that implicated to subsidized housing occupancy, so that each stakeholder gets information to plan the mitigation form to each factor. This research approach doing by qualitatively and quantitatively. The results show that the factors with the highest risk rating are: developer profitability not according to plan; contract late; the developer runs out of capital in project initial period; and housing area has a capacity <100 units. For the next, we need a study of the relationship and optimum value between price of houses, amount of PIF assistance that can be given, and the reasonable profit value as well as the solution and innovation of the PIF assistance policy that attracts developer groups with proportional small realization.